Morphological and pathogenic variability among Indian populations of Sclerotinia sclerotiorum causing stem rot of chickpea (Cicer arietinum) - MANDAL, A K; DUBEY, S C (The Indian Journal of Agricultural Sciences, 2016)
Stem rot caused by Sclerotinia sclerotiorum (Lib.) de Bary is one of the most important diseases of chickpea (Cicer arietinum L.). Irrespective of hosts of origin, isolates were proved to be pathogenic on chickpea cultivar BDG 1005. Majority of the isolates (20) produced white to dull white and fluffy growth while, only 4 isolates, namely, SS5 (Delhi), SS14 (Uttar Pradesh), SS20 (Haryana) and SS24 (West Bengal) produced suppressed growth without sclerotia which is the rare evidence in this pathogen. Isolates were grouped into three categories on the basis of their growth rate as slow, medium and fast growing. Sclerotia formed in different isolates were highly variable in number as well as in size. Isolate SS6 (Delhi) produced maximum number (50/plate) of smaller size (2.16 mm) sclerotia whereas, isolate SS15 (Himachal Pradesh) produced 21 sclerotia/plate with largest size (4.54 mm). Isolates were also variable in respect of their virulence. They were grouped into 7 pathotypes based on differential reactions on a set of 10 chickpea differential cultivars, namely, DCP 92-3, Pusa 212, Vishal, JG 74, KRW 108, GNG 469, JG 62, GPF 2, Pusa 1073 and WR 315. In the present study, cultivars DCP 92-3, Pusa 212, Vishal, JG 74, GPF 2 and WR 315 were considered to be host differentials for grouping of S. sclerotiorum into 7 pathotypes. Pathotype groups were not followed the continuity with that of geographical origin of isolates. It indicated that each region had mosaic of pathotypes. This is the first study in which the pathotypes of S. sclerotiorum populations were determined.